2020
DOI: 10.1080/00498254.2020.1767319
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and in vitro drug–drug interaction assessment of viloxazine

Abstract: 1. Viloxazine is currently being developed as a treatment for attention deficit/hyperactivity disorder (ADHD). The aim of these studies is to update the understanding of the rat and human metabolism and the in vitro drug-drug interaction profile of viloxazine to a degree where it meets current regulatory standards for such investigations. 2. In vivo absorption-distribution-metabolism-excretion (ADME) studies demonstrated that in humans 5-hydroxylation followed by glucuronidation is the major metabolic route. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Viloxazine ER is primarily metabolized to 5-hydroxyviloxazine by the cytochrome P450 (CYP) system isoenzyme CYP2D6 as a first step before its glucuronidation, with minor involvement of several other CYP isoenzymes. Subsequent glucuronidation to 5-HVLX-gluc is mediated by uridine 5′-diphospho-glucuronosyltransferase (UGT) 1A9 and UGT2B15 [32]. Viloxazine ER also functions as a reversible inhibitor of CYP1A2 (half maximal inhibitory concentration [IC 50 ] 0.269 µM) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viloxazine ER is primarily metabolized to 5-hydroxyviloxazine by the cytochrome P450 (CYP) system isoenzyme CYP2D6 as a first step before its glucuronidation, with minor involvement of several other CYP isoenzymes. Subsequent glucuronidation to 5-HVLX-gluc is mediated by uridine 5′-diphospho-glucuronosyltransferase (UGT) 1A9 and UGT2B15 [32]. Viloxazine ER also functions as a reversible inhibitor of CYP1A2 (half maximal inhibitory concentration [IC 50 ] 0.269 µM) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent glucuronidation to 5-HVLX-gluc is mediated by uridine 5′-diphospho-glucuronosyltransferase (UGT) 1A9 and UGT2B15 [32]. Viloxazine ER also functions as a reversible inhibitor of CYP1A2 (half maximal inhibitory concentration [IC 50 ] 0.269 µM) [32]. Conversely, methylphenidate is metabolized primarily by carboxylesterase 1 via de-esterification into ritalinic acid, which has little, if any, pharmacologic activity [30,33].…”
Section: Discussionmentioning
confidence: 99%
“…10 Viloxazine forms a unique N-carbamoyl glucuronide in humans, the chemical reactivity characteristics of which are similar to stable glucuronide conjugates and dissimilar from acyl glucuronides; therefore, it is a stable Phase II conjugate. 10 Viloxazine is rapidly metabolized and excreted in the urine, with no known active metabolites. 10 In vitro drug-drug interaction testing has shown that viloxazine is not a significant inhibitor or inducer of CYP isoenzymes, with the exception of being a strong inhibitor of CYP1A2.…”
Section: Introductionmentioning
confidence: 99%
“…10 Viloxazine is rapidly metabolized and excreted in the urine, with no known active metabolites. 10 In vitro drug-drug interaction testing has shown that viloxazine is not a significant inhibitor or inducer of CYP isoenzymes, with the exception of being a strong inhibitor of CYP1A2. 10 Viloxazine metabolism is not thought to rely solely on CYP2D6, alternatively, metabolism switching using multiple alternative CYP enzymes pathways may be activated if the major pathway is inhibited or not fully active.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, not feasible to assess the ECG effects of SPN-812 at C max above approximately 10-11 μg/mL. Based on these data as well as the findings from a SPN-812 metabolism assessment study, which showed that renal clearance was a major elimination route for SPN-812 (approximately 90% cleared within 24 hours of the dose, 100% within 96 hours), 19 the supratherapeutic dose of SPN-812 1,800 mg was selected and positive control (moxifloxacin) 17 was used.…”
Section: Dose Selectionmentioning
confidence: 99%